Probability and statistics for computer science - Johnson, James L. (Wiley, 2003)
Comprehensive and thorough development of both probability and statistics for serious computer scientists; goal-oriented: "to present the mathematical analysis underlying probability results". Special emphases on simulation and discrete decision theory. Mathematically-rich, but self-contained text, at a gentle pace. Review of calculus and linear algebra in an appendix.